Learning Online vs. Learning in Person: A Mixed-Methods Approach to Understanding How Student Preferences and Perceptions have Evolved Since the Pandemic - Kristi Bright; Jane Vogler (Online Learning)
Undergraduate enrollment in online courses has been trending upward over the past decade, despite declining enrollment overall. With the onset of COVID-19 during the Spring 2020 semester, more undergraduates were suddenly thrust into online courses. Although learning outcomes for face-to-face and online courses may not differ, some students may not be as efficacious or self-regulated in online contexts and thus, prefer to take classes face-to-face when possible. We aimed to understand undergraduates’ preferred course modality (online, face-to-face) and explored how those preferences may have changed since the COVID-19 pandemic. We also sought to determine whether students’ online self-efficacy and self-regulation skills varied by their preferred modality. Undergraduates (N = 1034) enrolled in various classes between 2019-2023 completed an online survey. Taking a convergent mixed-methods approach, we analyzed qualitative data related to reasons for their online or face-to-face preferences and quantitative data related to their self-efficacy and self-regulation for online learning. Results indicate student preferences have shifted from a clear preference for in-person classes to more equal distribution across modalities, with reasons related to perceived better support for learning, self-regulation, and need for human interaction (face-to-face) versus flexibility (online). Students’ self-regulation and self-efficacy for online learning did not consistently differ across preferred modality. Instructors can use these findings to inform course design, considering how they might incorporate such benefits regardless of their course modality. Institutions might also consider how to balance students’ need for flexibility but preference for face-to-face courses by implementing more hybrid options and providing various financial supports.